Advanced In vivo Use of CRISPR/Cas9 and Anti-sense DNA Inhibition for Gene Manipulation in the Brain - Walters, Brandon J.; Azam, Amber B.; Gillon, Colleen J.; Josselyn, Sheena A.; Zovkic, Iva B. (Frontiers in Genetics, 2016)
Gene-editing tools are essential for uncovering how genes mediate normal brain-behaviour relationships and contribute to neurodegenerative and neuropsychiatric disorders. Recent progress in gene-editing technology is now allowing neuroscientists unprecedented access to edit the genome efficiently. Although many important tools have been developed, here we focus on approaches that allow for rapid gene-editing in the mature nervous system, particularly CRISPR/Cas9 and anti-sense nucleotide-based techniques. CRISPR/Cas9 is a flexible gene-editing tool, allowing the genome to be manipulated in diverse ways. For instance, CRISPR/Cas9 has been successfully used to knock-out genes, knock-in mutations, overexpress or inhibit gene activity, and provide scaffolding for recruiting specific epigenetic regulators to individual genes and gene regions. Moreover, the CRISPR/Cas9 system may be modified to target multiple genes at one time, affording simultaneous inhibition and overexpression of distinct genetic targets. Although many of the more advanced applications of CRISPR/Cas9 have not been applied to the nervous system, the tool-box is widely-accessible, such that it is poised to help advance neuroscience. Anti-sense nucleotide-based technologies can be used to rapidly knock down genes in the brain and are simple to use. A main advantage of anti-sense based tools is their independence of viral packaging, allowing for rapid gene delivery with minimal technical expertise. Here, we describe the main applications and functions of each of these systems with an emphasis on their many potential applications in neuroscience laboratories.